Spectral problem for the mean field Hamiltonian - Astrauskas, Arvydas (Lietuvos matematikos rinkinys, 2021)
We consider the mean field Hamiltonian HV = κ ΔV + ξ(·) in l2(V ), where V = x is a finite set. Characteristic equations for eigenvalues and expressions for eigenfunctions of HV are obtained. Using this result, the spectral representation of the solution of the corresponding ("head transition’’) differential equation is derived.